SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JURUSAN BAGI SISWA PADA SMK NEGERI 1 KABUPATEN SELAYAR - Arfandy, Hamdan; Rahmawati (STMIK KHARISMA Makassar, 2023)
This study aims to implement a Decision Support System (DSS) application for choosing a major at SMK Negeri 1 Kabupaten Selayar using the Simple Additive Weighting (SAW) method. The application replaces the manual process of determining majors with an application-based model. With the SPK application for major determination, users can easily obtain complete and detailed information on which majors can be selected by students based on their grades, interests, and achievements. Additionally, the SPK application can be an alternative to replace the manual process in determining majors. The testing model used in this study is a black-box testing model, which is an approach to test whether each function in the program can run correctly. The author conducted several processes in this testing, such as testing incorrect functions, both inputs and outputs, interface errors, and errors in data structure or database access.